A decoupled Mechanical Shim core control strategy for a pressurized water reactor using feedforward compensation and a multimodel approach. (April 2019) - Wang, Pengfei; Wan, Jiashuang; Wei, Xinyu; Zhao, Fuyu
Highlights: A 1D transfer function core model was developed for decoupling control system design of PWRs. A decoupled MSHIM control strategy was proposed using feedforward compensation and a multimodel approach. Typical load change transients of AP1000 reactor with original and decoupled MSHIM strategies were simulated. The performance and feasibility of the decoupled MSHIM control strategy were assessed. Abstract: The advanced Mechanical Shim (MSHIM) core control strategy employs two separate and independent control rod banks, namely the MSHIM control banks (M-banks) and axial offset (AO) control bank (AO-bank), for automatic reactivity/temperature and axial power distribution control respectively. The M-banks and AO-bank are controlled by two closed-loop controllers, independently, called the coolant average temperature ( Tavg ) controller and the AO controller. Since the motion of the M-banks and AO-bank can both affect the Tavg and AO, an interlocking design between the Tavg controller and the AO controller is adopted in the MSHIM control strategy to avoid the interference between the two controllers during power maneuvers. This design can enhance the stability of the MSHIM control system by avoiding the simultaneous movement of the M-banks and AO-bank and keeping the priority of the M-bank movement. However, the AO control performance is degraded at the same time. In the present study, a feedforward compensation decoupling method and a multimodel approach have been used to eliminate the coupling effect between the two controllers in the MSHIM control system during a wide range of power maneuvers. A multiple feedforward compensation system has been designed with integration of the feedforward compensators for the Tavg and AO controllers at five equilibrium conditions using the multimodel approach. By implementing it in the MSHIM control system, the interlocking between the M-banks and the AO-bank can be released to realize the independent and decoupling control between the Tavg and AO. The effectiveness of the decoupled MSHIM control strategy has been verified by comparing its control performance with that of the original MSHIM control strategy during typical load change transients of the AP1000 reactor. The obtained results show that superior and decoupling control of the Tavg and AO can be achieved using the proposed decoupled MSHIM control strategy.